2021
DOI: 10.34197/ats-scholar.2020-0126oc
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact on Interventional Pulmonology Training

Abstract: Background: The impact of the coronavirus disease (COVID-19) pandemic extends beyond the realms of patient care and healthcare resource use to include medical education; however, the repercussions of COVID-19 on the quality of training and trainee perceptions have yet to be explored. Objective: The purpose of this study was to determine the degree of interventional pulmonology (IP) fellows’ involvement in the care of COVID-19 and its impact on fellows’ clinical education, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The number of pleural procedures performed essentially remained the same. A similar finding was noted in the survey study from the interventional pulmonology group ( 13 ). This could possibly relate to the fact that pleural procedures are generally unavoidable, as they are both diagnostic and therapeutic.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The number of pleural procedures performed essentially remained the same. A similar finding was noted in the survey study from the interventional pulmonology group ( 13 ). This could possibly relate to the fact that pleural procedures are generally unavoidable, as they are both diagnostic and therapeutic.…”
Section: Discussionsupporting
confidence: 88%
“…These changes directly or indirectly impacted the education and training of Pulmonary and Critical Care Medicine (PCCM) fellows. A recently published survey of interventional pulmonology fellows showed a decline in the number of procedures performed during the pandemic, especially therapeutic bronchoscopy, but the overall impact on training is unclear ( 13 ). The effect of the pandemic on general PCCM fellowship training is unknown.…”
mentioning
confidence: 99%
“…The reduction in the number of bronchoscopies is concordant with national guidelines and likely related to concerns about COVID-19 transmission during this aerosolizing procedure [ 13 , 21 , 22 ]. A survey of interventional pulmonology fellows similarly noted a decline in bronchoscopies since the pandemic [ 23 ]. The reduction in the number of intubations by fellows could be explained by hospital policies early in the pandemic assigning anesthesiologists to intubate all COVID-19 patients, or attempts by faculty to protect trainees from COVID-19 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…26 A recent survey on pulmonology trainees found that even though they were involved in COVID-19 patient care, the overall training toward skill acquisition was deficient and that modifications in educational models will be required in current and future health care crises, both global and local. 27 At this point, one may explore the possibility of an overhaul in the educational delivery system wherein early clinical exposure and training are mandated. The bulk of the didactic training occurs online and particularly for programs such as EM, where departments work on a shift basis around the clock, 24 hours a day, 7 days a week, and 365 days a year.…”
Section: Discussionmentioning
confidence: 99%